WHEN ETHICS CAN'T BE FOUND: Evaluative Gaps in Ordinary Life. (8th September 2022) - ZUCKERMAN, CHARLES H. P.
ABSTRACT: At a sparsely populated wake in Luang Prabang, Laos, the guests appeared to restrain themselves from evaluating the deceased's son‐in‐law to his face, even as they said to one another that he had neglected his mother‐in‐law and pocketed the funds for her wake to feed his methamphetamine habit. What are we to do with moments of apparent restraint like this, those meaningful silences in which signs of evaluation seem partially withheld, transfigured, or utterly absent? What do they mean for accounts of ordinary ethics? In unpacking the events of Paa's wake, I suggest that such moments force us to reckon with the relation between signs of evaluation and meta‐ethical accounts of them, as they also give flesh to the descriptive claim that humans are evaluative. Doing so makes clear that, at times, whether a particular person is being evaluative in a particular moment remains uncertain. At other times, people appear to be not only evaluative but so omnivorously evaluative—so fundamentally oriented to evaluation's possibility—that they keep their evaluations to themselves.